Development of nonlinear model for pH system - Mohamad Fikhri, Nor Azman (2010)
The control of pH process is a problem frequently encountered in the chemical process and biotechnology industries. It has been recognized as a challenging problem due to the time varying and nonlinear characteristics of the pH processes. This is particularly true when control has to be achieved in the neutral range (a pH betweens 6 to 8) when only strong acid and strong bases are present. The objectives of this research are development mathematical model for pH system, simulation studies under steady and unsteady state condition and validation of mathematical model through experimentation. The model of the pH process applied in this paper known as the principle of physico- chemical dynamic modeling. This model used acetic acid and sodium hydroxide for simulating the behavior of a simple pH process in a time optimal control loop. The mathematical model based on first principles is developed from acetate balance, sodium balance, acetic acid equilibrium, water equilibrium and electroneutrality equation. Then, the model equations are solved in MATLAB environment. The results from the MATLAB simulation program are compared with experimental result to validate the developed fundamental model. The results showed that most of the error between the model and experiment result are within 3% which proved the model has the capability to capture the dynamics of the process.